Urban Environment and Physical Activity of Petaling Jaya Residents - Rosli, Shamirah; Ling, Oliver Hoon Leh; Marzukhi, Marlyana Azyyati; Mohd Yusoff, Zaharah; Kwong, Qi Jie; Yinxue, Weng (International Journal of Sustainable Construction Engineering and Technology, 2023)
Physical activity and active lifestyle are imperative for good health. However, rapid urbanisation has prompted a significant decline in physical activity, particularly among those living in cities. Past studies have mainly focused on personal and social variables, built environment features, and green space features when examining how urban green spaces affect physical activity. Nevertheless, the statistical relationship between urban environment and physical activity remains unexplored, especially in the context of Malaysia. This study aims to address such gap by examining the relationship between urban environment and residents’ physical activity in Petaling Jaya, Selangor. Urban environment was evaluated based on four (4) indicators, namely green areas, sports facilities, facilities convenience, as well as the safety and distance to access the facilities. The data were obtained through observation and mapping the radius between the green areas and sports facilities to the neighbourhood area. Whereas, physical activity was evaluated based on the frequency and duration of two types of physical activity, namely vigorous activity and moderate activity. The data were obtained through a questionnaire survey, which were later analysed using frequency and cross-tabulation via the IBM SPSS Statistics software. The results showed that sections with more green areas and sports facilities as well as convenient environment tend to have active respondents. Meanwhile, sections with no green areas nor sports facilities still produced active respondents as they were willing to travel to nearby sections with green areas and sports facilities. The findings of this study hope to assist stakeholders, especially city planners, in improving urban environment for a healthier community.